2007
DOI: 10.1590/s0021-75572007000600010
|View full text |Cite
|
Sign up to set email alerts
|

Automedicação em crianças e adolescentes

Abstract: Objective: To determine the prevalence of self-medication in children and adolescents in the municipalities of Limeira and Piracicaba, state of São Paulo, and to correlate results with sociodemographic indicators and with the use of health care services (public or private).Methods: Descriptive population-based study of a simple random sample from the two municipalities, comprised of 772 inhabitants from 85 urban census sectors selected through cluster sampling. Inclusion criteria: age ≤ 18 years; interview wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
1
27

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 17 publications
5
5
1
27
Order By: Relevance
“…The prevalence of use of non-prescribed medication (29.3%) corroborates findings from other studies that this practice is common, irrespective of socioeconomic status 6,23 . The most common group of therapeutic prescribed drugs (systemic antibiotics and antiasthmatics) and the most common non-prescribed drugs (analgesics/antipyretics, antitussives/expectorants and vitamins) were similar to those reported in developed countries and in Brazil 6,15,16,17,23 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The prevalence of use of non-prescribed medication (29.3%) corroborates findings from other studies that this practice is common, irrespective of socioeconomic status 6,23 . The most common group of therapeutic prescribed drugs (systemic antibiotics and antiasthmatics) and the most common non-prescribed drugs (analgesics/antipyretics, antitussives/expectorants and vitamins) were similar to those reported in developed countries and in Brazil 6,15,16,17,23 .…”
Section: Discussionsupporting
confidence: 88%
“…This figure is lower than the findings of stud-ies carried out in developed countries 1,16 but similar to results found in two cities in the Brazilian state of São Paulo 23 . The prevalence of use of non-prescribed medication (29.3%) corroborates findings from other studies that this practice is common, irrespective of socioeconomic status 6,23 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The physician should always be consulted, either in person (Berardi et al, 2000) or at least by being notified as soon as possible about the intervention performed. However, it is important to note that some studies (Cascaes et al, 2008;Pereira et al, 2007;Osorio de Castro;Paumgartten;Silver, 2004) have shown that, even in special cases, self-medication is a common practice that needs to be streamlined.…”
Section: Data Compilation and Pharmaceutical Interventionmentioning
confidence: 99%
“…20 In the current study, mothers accounted for 12.0% of self-medication at 24 months (having increased from 2.6% at three months). Such an increase may indicate that mothers learn and incorporate treatment practices originally recommended by a physician, but which may not always be adequate to the current situation.…”
Section: Discussionmentioning
confidence: 51%